Value Cocreation and Wealth Spillover in Open Innovation Alliances1 - Han, Kunsoo; Oh, Wonseok; Im, Kun Shin; Chang, Ray M.; Oh, Hyelim; Pinsonneault, Alain (MIS Quarterly, 2012)
In this study, we investigate the economic and strategic value of open innovation alliances (OIAs), in which collaborators and competitors integrate in the pursuit of the codevelopment of technological innovations. Given that OIAs differ substantially from traditional, closed alliances in many aspects, including their strategic scope and scale, governing mechanisms, and member composition, it is important to understand and assess the potential value inherent in these new modes of collaboration. Furthermore, OIAs evolve over time as the participating members are free to enter and leave at will. Therefore, we also examine the on-going value creation and wealth spillover that result from changes in membership. Moreover, we investigate how a firm’s participation in an IT-based open alliance alters the market value of its rivals operating within the same marketplace. To gain additional insight into the factors that moderate the market valuation of OIA participation, several contextual factors, including the degree of partner heterogeneity, innovation type, and degree of openness of the OIAs are used to account for variability in abnormal returns. Based on 194 observations, we found that allying firms realize significant positive abnormal returns when their entry into an OIA is made public. The results also suggest that substantial excessive returns accrue to the allying firms with the belated entry of a market leader firm. Furthermore, we discovered that a firm’s entry into an OIA increases, rather than decreases, the market valuation of its rivals. Interestingly, an incumbent rival that did not participate in the alliance appears to gain greater “free-riding” benefits from the OIA, as compared to peer rivals. Innovation type and openness were significantly associated with the amount of abnormal returns accruing to allying firms, while no significance was found for partner heterogeneity. Finally, we conclude with a discussion of the implications of our findings for research and practice with respect to value cocreation in multifirm environments.